Teaching as a performative art - James Godfrey (SCENARIO: Journal for Performative Teaching, Learning, Research)
This paper reports on diagnostic workshops conducted at a teacher training centre in Istanbul focusing on how Applied Theatre methods can support English Language Teacher Education in the areas of self-awareness and self-reflection. The workshops provided 12 participant English Language teachers experience of Applied Theatre methods and techniques to elicit feedback on their pedagogic value and efficacy in teaching. Through dialogue and reflection, participants identified the performative and meta-performative skills they valued from the workshops. While Applied Theatre methods have a proven track record in many contexts, they are rarely utilized in teacher development programmes. Feedback from the workshops revealed that Applied Theatre methods, notably Forum Theatre, provide embodied, participant-led, solution-oriented, multiple voiced opportunities for reflection and dialogue on critical incidents teachers’ face. In addition, participants highlighted performative skills pertaining to developing awareness of self, others and setting that are disregarded in current competence-based teacher education programmes. Participants also uncovered meta-performative skills reflecting on why teachers act in the way that they do. The workshops provide an initial template to create teacher development programmes incorporating Forum Theatre and other Applied Theatre techniques.